Menilai Kinerja Keuangan di Saat Pandemi dan Menuju Digitalisasi BUMDes - Desiderius Novena Kosta; Victoria Ari Palma Akadiati; Imelda Sinaga (UNHI Press, 2022)
Abstract The purpose of this study was to determine the financial performance of BUMDes in Balekencono Village, Batanghari District, East Lampung Regency based on the analysis of liquidity ratios, solvency ratios, activity ratios and profitability ratios. The population used in this study is the financial statements of BUMDes in Balekencono Village in 2019-2020. The data used in this study is secondary data, namely by taking or requesting ready-made financial data related to research problems in the form of financial statements from BUMDes consisting of income statements and balance sheets for 2019-2020. The results of this study are based on calculations regarding the Liquidity Ratio in 2019-2020 which is measured using the Current Ratio, showing declining results and means good performance. The Solvency Ratio in 2019-2020 which was measured using the Debt To Equity Ratio, showed increased results and meant that the performance was quite good. The Activity Ratio in 2019-2020 as measured using Total Asset Turn Over shows declining results and means that the performance is quite good. Profitability Ratios for 2019-2020 as measured using Return On Assets showed declining results and interpreted as very good performance.